2020
DOI: 10.3390/cancers12030615
|View full text |Cite
|
Sign up to set email alerts
|

Haprolid Inhibits Tumor Growth of Hepatocellular Carcinoma through Rb/E2F and Akt/mTOR Inhibition

Abstract: Background: Hepatocellular carcinoma (HCC) represents a major health burden with limited curative treatment options. There is a substantial unmet need to develop innovative approaches to impact the progression of advanced HCC. Haprolid is a novel natural component isolated from myxobacteria. Haprolid has been reported as a potent selective cytotoxin against a panel of tumor cells in recent studies including HCC cells. The aims of this study are to evaluate the antitumor effect of haprolid in HCC and to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In papillary carcinoma (PTC), CITED1-meditaed interference of p21 and p27 expression can increase the level of phosphorylated Rb and the transcriptional activity of E2F1, which leads to PTC cell proliferation (Li et al, 2018). Xing et al (2020) reported that in HCC cells, haprolid upregulates the expression of p21 and p27 and inhibits the G1/S phase transition of cells, which may be related to the downregulation of Rb/E2F expression. Therefore, it can be speculated that CENPN reduces the level of phosphorylated Rb and inhibits E2F1 transcription by downregulating the activities of the p27-CDK4/cyclin D1 and p21-CDK2/cyclin E axes, thus inhibiting c-myc as well as cyclin E, inhibiting cell proliferation, and ultimately affecting the prognosis of liver cancer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In papillary carcinoma (PTC), CITED1-meditaed interference of p21 and p27 expression can increase the level of phosphorylated Rb and the transcriptional activity of E2F1, which leads to PTC cell proliferation (Li et al, 2018). Xing et al (2020) reported that in HCC cells, haprolid upregulates the expression of p21 and p27 and inhibits the G1/S phase transition of cells, which may be related to the downregulation of Rb/E2F expression. Therefore, it can be speculated that CENPN reduces the level of phosphorylated Rb and inhibits E2F1 transcription by downregulating the activities of the p27-CDK4/cyclin D1 and p21-CDK2/cyclin E axes, thus inhibiting c-myc as well as cyclin E, inhibiting cell proliferation, and ultimately affecting the prognosis of liver cancer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific molecular mechanisms remain unclear. Various cancer-related signaling pathways, such as JAK/STAT ( 42 ), PI3K/Akt ( 43 ), JNK ( 44 ), Wnt ( 45 ), and MAPK/ERK ( 46 ), have been revealed to play pivotal roles in tumor cell invasion and migration. The effect of CENPM in the aforementioned pathways will be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 2DG resulted in the suppression of total and glycolytic adenosine triphosphate (ATP) production, but not mitochondrial oxidative ATP production in the Huh7 cells ( Figure 2 A ), in agreement with no effects on the mitochondrial oxygen consumption ratio ( Figure 2 B ). Treatment with 2DG-PLGA-NPs resulted in the augmentation of AMP-activated protein kinase (AMPK) phosphorylation and the expression of endoplasmic reticulum (ER) stress-related chaperones, and the attenuation of mammalian target of rapamycin (mTOR) activity and its downstream molecules such as S6, Rb, cyclin D1, proliferating cell nuclear antigen, and vascular endothelial growth factor-A, 19 , 20 , 21 , 22 in xenograft liver tumors ( Figure 2 C ). Treatment with 2DG-PLGA-NPs decreased CD34-positive vessel density ( Figure 2 D ) and increased reactive oxygen species (ROS) production ( Figure 2 E ) in xenograft liver tumors.…”
Section: Resultsmentioning
confidence: 99%